How alternative is alternative? the role of entrepreneurial development, form, and function in the emergence of alternative marketscapes - Mars, Matthew M.; Schau, Hope Jensen (Emerald Publishing, 2022)
There is a growing class of entrepreneurs who, for a range of reasons, are working to create viable alternatives to mainstream production and consumption models. Existing literature that cuts across multiple fields illustrates the unique features, challenges, and value propositions of alternative forms of entrepreneurship. Yet, the complexities associated with how alternative marketscapes form and function remain "fuzzy." Volume 29 of Advances in the Study of Entrepreneurship, Innovation and Economic Growth asks, "How alternative are alternative marketscapes?" In doing so, greater clarity is gained on the underlying economic, organizational, and social conditions and environments within which alternative marketscapes develop. The volume includes theoretical arguments and case studies that view alternative entrepreneurship not as co-existing with, but rather transforming mainstream entrepreneurship, and challenge the understanding of alternative entrepreneurship as being inherently altruistic. The exploration of ingenuity and innovation, in conjunction with cases that illustrate the diversity of alternative market contexts, generates organizational and system-level applications. The volume authors provide entrepreneurs and companies a concise understanding of alternative marketscapes that paves the way for development and success.
Keywords: Entrepreneurship; Business & Economics; Entrepreneurship; Aufsatzsammlung